Clinical characteristics of and risk factors for secondary bloodstream infection after pneumonia among patients infected with methicillin-resistant Staphylococcus aureus. Issue 12 (December 2022) - Huang, Fangfang; Shen, Ting; Hai, Xin; Xiu, Huiqing; Zhang, Kai; Huang, Tiancha; Chen, Juan; Guan, Zhihui; Zhou, Hongwei; Cai, Jiachang; Cai, Zhijian; Cui, Wei; et al.
Abstract: Purpose: To investigate the clinical features and risk factors for methicillin-resistant Staphylococcus aureus (MRSA) pneumonia (MP) with secondary MRSA bloodstream infections (MRSA-BSI) (termed MP-BSI) compared with MP alone and to study the incidence of MP-BSI among patients with MP. Methods: This was a retrospective, single-center study with clinical data derived from previous medical records. The cases were divided into groups: MP alone and MP-BSI. The determination of independent risk factors for MP-BSI relied on logistic regression analysis. Additionally, the crude outcomes were compared. Results: A total of 435 patients with MP were recruited, with 18.9% (82/435) having MP-BSI. The median age was 62 (interquartile range, 51, 72) years, and 74.5% of the patients were male. Multivariate analysis revealed that immunosuppression, community-acquired MP (CA-MP), time from initial to targeted antibiotic use, high Sequential Organ Failure Assessment (SOFA) score, increased respiratory rate, and elevated γ-GT level (all p < 0.05) were independent risk factors for MP-BSI, while targeted treatment with linezolid was a protective factor. Patients with MP-BSI had a longer duration of hospitalization (median days, 27.5 vs. 19, p = 0.001), a higher 28-day mortality rate (24.4% vs. 11.0%, p = 0.001), and a higher in-hospital mortality rate (26.8% vs. 14.7%, p = 0.009) than those with MP alone. Conclusion: Secondary MRSA-BSI among patients with MP is not rare. Immunosuppression, CA-MP, time from initial to targeted antibiotic use, high SOFA score, increased respiratory rate and elevated γ-GT level are all independent risk factors for MP-BSI; however, linezolid, as a targeted antibiotic, is a protective factor. Moreover, patients with MP may have worse clinical outcomes when they develop MRSA-BSI. Highlights: Secondary MRSA bloodstream infection is not uncommon in MRSA pneumonia. Some factors (e.g., high SOFA score) are predictors of bloodstream infection. Linezolid as a targeted antibiotic is a protective factor. Secondary bloodstream infection will worsen clinical outcomes of pneumonia. Abstract : Methicillin-resistant Staphylococcus aureus, Pneumonia, Bloodstream infections, Risk factors.